2013
DOI: 10.1080/08276331.2014.892313
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial aspects of entrepreneurial potential

Abstract: This study presents a theoretical model regarding the entrepreneurial potential construct, and the main psychosocial aspects that contribute towards an individual's preparedness to engage in activities typically associated with entrepreneurship. The general question addressed in this study is: How to explain the entrepreneurial potential construct theoretically, and how to assess it empirically? This study seeks to contribute by creating an instrument (the EPAI -Entrepreneurial Potential Assessment Inventory) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(82 citation statements)
references
References 67 publications
2
72
0
8
Order By: Relevance
“…Work and entrepreneurial experiences, perseverance and expected time lag to first revenue It is known that complication arises from the entrepreneurial process perceived as both increasing risks and unexpected challenges (Santos, Caetano & Curral, 2013;Huang & Knight, 2015). Therefore entrepreneurial experience and self-efficacy becomes critical for an entrepreneur to improve both risk appetite and skills to implement his/her entrepreneurship plan (Hallak, Lindsay & Brown, 2011).…”
Section: A Brief Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Work and entrepreneurial experiences, perseverance and expected time lag to first revenue It is known that complication arises from the entrepreneurial process perceived as both increasing risks and unexpected challenges (Santos, Caetano & Curral, 2013;Huang & Knight, 2015). Therefore entrepreneurial experience and self-efficacy becomes critical for an entrepreneur to improve both risk appetite and skills to implement his/her entrepreneurship plan (Hallak, Lindsay & Brown, 2011).…”
Section: A Brief Literature Reviewmentioning
confidence: 99%
“…While passion plays a limited role in shaping investor decision-making (Chen et al, 2009) perseverance of entrepreneurs has become a determining factor, and it is not easy to maintain perseverance due to rising pressure of work-life experiences and lack of coping strategies (Jennings & McDougald, 2007;Santos, Caetano & Curral, 2013). Unfortunately, perseverance and self-efficacy are not costless (Markman, Baron & Balkin, 2005).…”
Section: A Brief Literature Reviewmentioning
confidence: 99%
“…Both theoretical and empirical studies have shown that these values are hard to establish without work experiences and coping strategies (Jennings and McDougald, 2007;Santos et al 2013). Moreover, since they are not without cost (Markman et al 2005), entrepreneurs' decisiveness will also be neither inexpensive nor time-costless (Westhead et al 2009;Sullivan-Taylor and Branicki 2011;Schindehutte et al 2006).…”
Section: Transforming Sociocultural Values and Decisivenessmentioning
confidence: 99%
“…The learning process involves the understanding of complication arising from the entrepreneurial process, in the forms of increasing risks and unexpected challenges (Santos et al 2013;Huang and Knight 2015).…”
Section: Chance Of Success and Lessons From Others' Failuresmentioning
confidence: 99%
“…Work and entrepreneurial experiences, perseverance, and expected time lag to first revenue It is known that complication arises from the entrepreneurial process perceived as both increasing risks and unexpected challenges (Santos et al 2013;Huang and Knight 2015). Therefore, entrepreneurial experience and self-efficacy becomes critical for an entrepreneur to improve both risk appetite and skills to implement his/her entrepreneurship plan (Hallak et al 2011;Fayolle and Gailly 2015).…”
Section: Entrepreneurial Attitudes and Environmental Factors That Affmentioning
confidence: 99%